Production structure, output and profits - A note - Ilhan Dögüs (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2021)
This paper argues that the case of product differentiation of concentrated markets (i.e., innovation competition) is one where production per unit of profit of non-financial corporations is lower than in competitive mass production and profit share is not an increasing function of capacity utilisation. Rather the desired excess capacity is higher compared since the break-even point where total costs and revenues equalize tends to be lower. The argument is supported with descriptive annual data for the period 1947-2019 in the USA.
Keywords: D24; E12; L11; 330; product differentiation; market structure; capacity utilisation; profits